Steps:
1. Slope intercept formula=
Y=mx+ b
2. M= slope b= y-intercept
3. Now do substitution
4. Your answer is
Y=2/3x + 7
G(x) = 3x² - 5x + 7
b) g(-2) ==> Substitude -2 into x
g(-2) = 3(-2)² - 5(-2) + 7
g(-2) = 12 + 10 + 7
g(-2) = 29
c) g(4) ==> Substitude 4 into x
g(4) = 3(4)² - 5(4) + 7
g(4) = 48 - 20 + 7
g(4) = 35
d) g(-x) ==> Substitude -x into x
g(-x) = 3(-x)² - 5(-x) + 7
g(-x) = -3x² + 5x + 7
e) g(1 - t) ==> Substitude 1 - t into x
g(1 - t) = 3(1 - t)² - 5(1 - t) + 7
g(1 - t) = 3(1 - 2t + t²) - 5 + 5t + 7
g(1 - t) = 3 - 6t + 3t² - 5 + 5t + 7
g(1 - t) = 3t² - t + 5
Answer:
negative
Step-by-step explanation:
A negative value raised to an even exponent is positive
A negative value raised to an odd exponent is negative
= - 512 ← negative
= 256 ← positive
Answer:
b
Step-by-step explanation: